Broken Gears : The Value Added of Higher Education on Teachers' Academic Achievement - Balcazar, Carlos Felipe (World Bank Group, Washington, DC, 2015)
Good teachers are essential for high-quality educational systems. However, little is known about teachers' skills formation during college. By combining two standardized tests for Colombian students, one taken at the end of senior year in high school and the other when students are near graduation from college, this paper documents the extent to which education majors relatively improve or deteriorate their skills in quantitative reasoning, native language, and foreign language, in comparison to students in other programs. Teachers' skills vis-a-vis those in other majors deteriorate in quantitative reasoning and foreign language, although they deteriorate less for those in math-oriented and foreign language-oriented programs. For native language, there is no evidence of robust differences in relative learning mobility.